Motivational determinants and students' attitude to physical education - Abele, Agita; Rubana, Inta Mara (Acta Universitatis Carolinae. Kinanthropologica, 2009)
Today physical education is of great concern as the modern lifestyle tends to be sedentary and involves children into very little physical activities. Evasion of compulsory physical education (PE) classes has evolved into a noticeable tendency among the 1st to 9th grade students. An insufficient understanding of the significance of a healthy lifestyle is also observed. Because of these students' inner motivation and formation of attitude towards sports is very important. The objective of our research is to analyze basic motivation determinants and students' attitude towards sports classes in complex with determining ways of improving PE lesson attractiveness. The following research tasks were forwarded: 1. Establishing the main motivational determinants for attendance of and attitudes at physical education classes from students and teachers viewpoints. 2. Creating recommendations for sport education program development and sport classes' organization in Latvia. To accomplish the task 26 sport teachers were interviewed. An open-answers inquiry was also done on 937 school children aged 12–16 (285 students in grades 5 and 6, 358 students in grades 7 and 8, and 294 students in grade 9). In the present research we evaluated viewpoints of the social cognitive theory (SCT), theory of reasoned action (TRA) and theory of planned behaviour (TPB) to investigate the psychological and social factors by which adolescents' motivation in physical activity transfers into regular attendance of sports classes. Inquiry results showed that students' attitude towards PE lessons with increasing age has a negative dynamics, students' opinions of what a good PE lesson should be like change as well. Teachers on the other hand point out that they cannot apply many of their better ideas in lesson organization because they need to be organized according to the Ministry's of Education standards and evaluation criteria. In general we concluded that it is necessary to make the PE lessons more appealing to students by introducing more sports games into them, reducing the amount of norms to be met during performance tests, and emphasizing the importance of student's willingness to get involved and trying to do their best in the lessons and as opposed to their physical abilities in the assessment. In changing the lesson content teachers should also take into account that with changing age students' interests change as well, and make sure these interests are met for all age groups. Key words: students' attitude, motivation, health, physical education and sports.
Keywords: behaviorální výzkum; Humans; Physical Education and Training; rozhovory jako téma; tělesná výchova; motivace; výchova a vzdělávání; Students; Sports; studenti; Education; Attitude; Behavioral Research; Latvia; Statistics as Topic; statistika jako téma; Lotyšsko; lidé; Motivation; Interviews as Topic; sporty; postoj